The Development of Animation-Based Learning on Students’ Numeracy Literacy Skills - Syahriani Sirait; Ely Syafitri; Khairun Nisa (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is to provide animation-based learning media to enhance the autonomous curriculum programme in the area of numeracy. The study's findings will be reliable and useful in the real world. The ADDIE paradigm is being used in this study of development. This study had three phases: The fourth-grade students of a state elementary school in Banjar during the 2022–2023 school year made up the study's population. The data was collected from a group of 35 fourth graders. The data was analysed using quantitative and qualitative methods. The Smart Apps Creator software is being used in this development study; ultimately, researchers use it to create animated educational materials. Expert validation results show that the data generated from these trials are quite valid, with an average of 90% accuracy. In addition, 93 % of students rated animation-based learning material as effective, while 90 % of teachers rated it as useful. Students then finish traditionally, scoring an average of 94% in the very effective category on the numeracy literacy test. This figure establishes animation as a realistic, practical, and successful learning medium for fourth-grade elementary school fractions.